Evaluation of the gold installment pricing policy and its implications for market competitiveness and growth - Wahyunitasari, Eka Dita; Haryanti, Peni; Muhammad, Atha Mahdi (Alkasb: Journal of Islamic Economics, 2024)
This study aims to evaluate the gold installment pricing policy at Bank Syariah Indonesia (BSI) and analyze its implications for market competitiveness and growth. The gold installment pricing policy plays an important role in attracting customer interest and maintaining the stability of the gold market in the Islamic banking sector. This study uses a secondary research method with a descriptive analytical approach from BSI's financial statements and internal policies. The results of the study indicate that a competitive gold installment pricing policy can increase BSI's competitiveness in the Islamic banking market, while simultaneously driving significant market growth. However, there are challenges in maintaining a balance between pricing in accordance with Islamic principles and fluctuating market dynamics. The implications of these findings emphasize the importance of adjusting pricing policies to be in line with market needs and sharia principles. Competitive policies not only expand market share but also maintain BSI's position as a leader in the sharia banking sector.